A case study on biophilic design elements in general circulation areas in a hospital to promote positive health outcomes - Navia, Cyrene Danielle P. (College of Home Economics, University of the Philippines Diliman, 2018)
This study examined the positive and negative effects of Biophilic Design elements in general circulation areas of a hospital to the well-being of patients to produce positive health outcomes. Recent studies suggest that incorporating nature (i.e. Biophilic Design) relates to creating supportive environments that can promote the well-being of a user by reducing anxiety, increasing a sense of control, and providing positive distractions. The study used observation, a survey, and a short interview to gather data on outpatients staying in two general circulation areas in the ground floor of a hospital in Parañaque. Twenty one respondents each came from the waiting area and the lobby, to a total of 42 respondents. The findings from this case study showed that respondents identified Biophilic Design elements such as day lighting, simulation of weather, and information richness as elements that elicited positive responses. The absence of Biophilic Design elements such as refuge, transitional space, and mobility were identified as stressors and elicited negative feelings from them. This means that Biophilic Elements applied in lighting, ventilation, and proper space planning (in traffic flow and circulation) can affect the stress levels and mood of the patients, and thus affect their health outcome. Other emerging elements were the newness of space, incorporating positive distractions, and aesthetics and décor. This study recommends further research on biophilic design and its impact in various healthcare settings, and highlights better strategies in designing general circulation areas of hospitals.